Conformist innovation: an institutional logics perspective on how HR executives construct business school reputations. Issue 13 (20th July 2018) - Martin, Graeme; Siebert, Sabina; Robson, Ian
Abstract: In this paper, we explore whether Legge's classic 1970s criticism of human resource (HR) executives as 'conformist innovators' is still relevant. Drawing on institutional logics, we analyse HR managers' rationales for choosing particular university business schools to provide senior executive development. Our mixed-methods study demonstrates that senior HR managers socially construct and enact business school reputations by drawing on strategic rationales. These rationales are embedded in societal, field and organizational logics, especially the extant reputational rankings of international business schools and an 'ideal' template of elite business schools. We find that these rationales, and the decisions they evince, tend to confirm the traditional picture of conformist innovation among HR executives. We discuss the implications for the reputation of HR as a profession, their employers and business schools.